A Prototype Instrument for Measuring Service Quality by Generation X Parents: A Case Study at the International School of Macao - Stribbell, Howard; Duangekanong, Somsit (Asian Journal of Contemporary Education, 2022)
This quantitative research aimed to advance the use of the service quality construct to measure the perceived service quality of K-12 international schools by Generation X parents. It proposed an approach that contextualised previously published scale items for private healthcare into educationally relevant scale items. The revised scale items were developed and confirmed through an Item Objective Congruence Test (IOC) by industry experts. The instrument was tested for reliability through a pilot test and then administered to 499 parents in a school. The results used Exploratory Factor Analysis (EFA) to reduce the complexity of the standard 5 service quality (SERQUAL) factors into 3 factors: Responsibility, Assurance and Professionalism, Empathy and Facilities which accounted for 65% of the variance of the SERVQUAL variables amongst Generation X parents at The International School of Macao. The revised instrument can be used to effectively measure parents’ perception of service quality in an international school setting.